Kejujuran dalam Bingkai Hak Memilih-Dipilih (Pelajaran dari Pemilukada Bengkulu Selatan) - Abdul Ghoffar (The Constitutional Court of the Republic of Indonesia, 2016)
This article discusses two decision of the Constitutional Court. First, the Constitutional Court Decision No. 57/PHPU.D-VI/2008 on Election Dispute of Regional Head of South Bengkulu, which disqualify the candidate elected, Dirwan Mahmud, because it proved to be dishonest if he had been sentenced 7 years in prison, to the detriment of the rights of citizens to choose obtain correct information about the future leaders will be chosen. Second, the Constitutional Court Decision No. 4/PUU-VII/2009 about the review of Article 12 sub-article g and Article 50 paragraph (1) sub-article g election law, and Article 58 sub-article f Local Government Act, which gives the right choosen to convict (common criminal) after five years sentence expired with the condition that he honestly convey to the public if he is a former convict. This paper focuses on the importance of honesty in the implementation of the right to vote and be elected citizens.